Development of Pesticide Sprayer Robot Prototype for Chilli Farm Agricultural Application - Mashori, Sumaiya; Azmi, Muhammad Amar Aizad; Sahari, Norain; Jalaludin, Nor Anija; Sim, Sy Yi; Norjali, Rasida (International Journal of Integrated Engineering, 2023)
Accidental spills of chemicals, leakages, poor spraying equipment, or a lack of knowledge about personal protection equipment usage can expose farm workers to pesticides either in open fields or greenhouse. Pesticides may affect their health, particularly on dermal contact and respiratory system. Besides that, traditional pest management for massive agriculture industry requires a big number of employees, large quantities of pesticides, and the risk of inefficient and uneven pesticides coating. Therefore, a pesticide spraying robot, which is equipped with two ultrasonic sensors is developed to spray pesticide independently and allows the workers to maximize pesticide usage on the agricultural application such as chilli farm. The prototype is designed to automatically moves and operate in two modes, either automatic or manual. For automatic mode, the robot travel and operated independently without human control or intervention. While for manual mode, the Blynk application is used to remotely control the robot’s movement and spraying insecticide. In this research, the garlic extract and dishwashing liquid detergent were used as organic insecticides since they are effective and safe for plants and the environment. The study discovered that for a 50 cm two-month chilli plant, a three-seconds pesticide setting was appropriate, with 30 ml pesticide applied per chilli plant.